Original paper Hybrid techniques in the treatment of thoracic aortic aneurysm – own experience - Kuśmierczyk, Mariusz; Demkow, Marcin; Woźniak, Sebastian; Michałowska, Ilona; Małek, Łukasz A.; Rowiński, Olgierd; Rużyłło, Witold; Różański, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2009)
Aim: Two cases of patients with thoracic aortic dissection treated with hybrid technique consisting of surgical aortic valve graft implantation (Bentall procedure) with a transfemoral stent-graft implantation as a second stage procedure are presented. Methods and results: In both cases thoracic aortic dissection was diagnosed. First patient underwent aortic valve graft implantation (Bentall procedure) with transposition of brachiocephalic trunk and left common carotid artery. In the second case Bentall procedure with by-pass to the right coronary artery and transposition of the great arteries to the aortic prosthesis with the use of Dacron prostheses was performed. Both patients had a stent-graft implantation to the thoracic descending aorta covering the left subclavian artery as a second stage procedure. Conclusions: The use of stent-grafts and hybrid technique in patients with thoracic aortic aneurysms and dissections should be more frequent. It is related to the lower risk of death and neurological complications in comparison to conventional surgical treatment of the thoracic aortic aneurysms.